IMPLEMENTASI KRIPTOGRAFI MODERN DENGAN METODE RSA PADA DATA CITRA DIGITAL - Zeyan Zico Deskiva; Zekson Arizona Matondang (UPPM, 2018)
The development of technology at this time has greatly helped humans in various fields, especially in the field of communication, which only requires a short time in exchanging information. The information is stored in digital format, such as text, images, video, audio and other multimedia. Especially with regard to digital images, there are many applications to change images easily. This study aims to create an application that can be used to secure these images, especially in digital images, and one of the methods that can be used is cryptography. Cryptography is an art in maintaining the confidentiality of data. To maintain the confidentiality of the data cryptography changes the data that has meaning (plaintext) into a form whose meaning is unknown (ciphertext). This ciphertext will be sent to the recipient. The method used in this case is the asymmetric method with the Rivest Shamir Adleman (RSA) algorithm. The difficulty in factoring numbers into prime factors is the security location of the RSA algorithm, which aims to obtain public and private keys.